Islamic microenterprise institutions: risks and challenges in the post-COVID-19 - Shafiai, Syahiru; Johari, Maimunah; Mohd Ruslan, Rafiatul Adlin; Abdul Aziz, Muhammad Ridzuan; Muhamed, Ariff Azly; Fianto, Bayu Arie (2023)
This paper aims to explore the risks and challenges faced by microenterprise institutions within the context of digitalization post-COVID-19, offering valuable insights into the existing literature on this subject. Furthermore, the study incorporates a behavioural perspective when evaluating the efficiency of microenterprise institutions that provide banking services. The study relies solely on related literature and highlights the risks and challenges in Islamic microenterprise institutions. Reviews of previous studies normally have their own terminology in research methodology. This section covers the various facets of digital finance risk, including cybersecurity threats, data privacy concerns, and operational vulnerabilities, as well as how these risks may influence clients' trust, adoption, and engagement with technology-based banking services. The findings of this research shed light on the multifaceted risks and challenges faced by microenterprise institutions. Digital finance and its role in enhancing financial inclusion offer numerous advantages to users of financial services, digital finance providers, governments, companies, and the overall economy. The highlight of this study is several persistent challenges that, when effectively addressed, can further improve the effectiveness of digital finance for individuals, businesses, and governments alike. The digital finance issues highlighted in this article hold significance in ongoing discussions and country-level initiatives aimed at promoting greater financial inclusion through digital finance in developing and emerging economies. A compelling avenue for future research could involve investigating the connection between digital finance and economic crises and examining whether digital finance plays a role in spreading financial contagion in times of crisis, and to suggest possibilities for reform.